2021
DOI: 10.1155/2021/6657529
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of TOPK Caused by Hyperglycemia Blocks Diabetic Heart Sensitivity to Sevoflurane Postconditioning by Impairing the PTEN/PI3K/Akt Signaling

Abstract: The cardioprotective effect of sevoflurane postconditioning (SPostC) is lost in diabetes that is associated with cardiac phosphatase and tensin homologue on chromosome 10 (PTEN) activation and phosphoinositide 3-kinase (PI3K)/Akt inactivation. T-LAK cell-originated protein kinase (TOPK), a mitogen-activated protein kinase- (MAPKK-) like serine/threonine kinase, has been shown to inactivate PTEN (phosphorylated status), which in turn activates the PI3K/Akt signaling (phosphorylated status). However, the functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It is well known that the PTEN/PI3K/AKT axis can regulate cell behaviors, and act as a protective axis for cell survival. 68,69 As a non-redundant, plasma-membrane lipid phosphatase, PTEN is a PI3K inhibitor which can suppress the downstream protein kinases, such as AKT and 3-phosphoinositide dependent kinase1 (PDK1). 70,71 PTEN is involved in many processes, such as cell proliferation, apoptosis, pyroptosis, autophagy, etc.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…It is well known that the PTEN/PI3K/AKT axis can regulate cell behaviors, and act as a protective axis for cell survival. 68,69 As a non-redundant, plasma-membrane lipid phosphatase, PTEN is a PI3K inhibitor which can suppress the downstream protein kinases, such as AKT and 3-phosphoinositide dependent kinase1 (PDK1). 70,71 PTEN is involved in many processes, such as cell proliferation, apoptosis, pyroptosis, autophagy, etc.…”
Section: Paper Food and Functionmentioning
confidence: 99%
“…Eventually, 39 articles were further excluded; of them, 12 articles were due to difference of study protocols, 11 articles had TTC staining only, 6 articles were ex-vivo studies, 5 articles did not report infarct size, 2 articles were no sample size per group, 2 articles could not acquire full text, and 1 article used animal model with the risk factors of cardiovascular diseases ( Figure 1 ). As a result, 37 literatures [(14 SPreC studies ( 10 , 17 , 19 , 21 , 22 , 24 32 ), 20 SPostC studies ( 11 , 33 51 ), and 3 both the SPreC and SPostC studies ( 18 , 20 , 23 )] met our selection criteria and were included in the analysis. Of 37 included studies, 7 studies provided the associated information of infarct size merely in figures, including 3 SPreC studies ( 10 , 30 , 31 ) and 4 SPostC studies ( 37 , 45 , 49 , 50 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our study con rmed that OED can attenuate the diabetic cardiomyopathy possibly via activating Nrf2 pathway. However, researches have reported that Nrf2 activation may depend on evaluating the upstream signaling pathways, such as PI3K 59 , β-RECP 60 , SIRT1 61 and GSKβ 54 . It requires experimental validation that whether OED activates the upstream signaling pathways to further affect Nrf2 or not.…”
Section: Discussionmentioning
confidence: 99%